Modification of perceived beer bitterness intensity, character and temporal profile by hop aroma extract - Oladokun, Olayide; Tarrega, Amparo; James, Sue; Cowley, Trevor; Dehrmann, Frieda; Smart, Katherine; Cook, David; Hort, Joanne (Elsevier, 2016)
The effect of hop aroma on perceived bitterness intensity, character and temporal profile of beer was investigated. A hop aroma extract was added at 3 levels (0, 245, 490 mg/L) to beers at low, medium and high bitterness. Beers were evaluated for perceived bitterness intensity, harshness, roundedness and linger by a trained panel using a rank-rating technique at each bitterness level, with and without nose clips. The use of nose clips enabled the olfactory aspect to be decoupled from taste and mouthfeel aspects of bitterness perception. Results showed significant modification of perceived bitterness in beer by hop aroma depending on the inherent level of bitter-ness. These modifications were mainly driven by olfaction – in an example of taste-aroma interactions, as well as certain tactile sensations elicited by the hop aroma extract in the oral cavity. At low bitterness, beers with hop aroma added were perceived as more bitter, and of ‘rounded’ bitterness character relative to those without hop aroma. When judges used nose clips, this effect was completely eliminated but the sample was perceived to have a ‘harsh’ bitterness character. Conversely, at high bitterness, even when nose clips were used, judges still perceived beers containing hop aroma to be more bitter. These increases in bitterness perception with nose clips indicates the stimulating of other receptors, e.g. trigeminal receptors by hop aroma extract, which in tandem with the high bitterness, cause perceptual interactions enhancing bitterness intensity and also affecting bitterness character. Bitterness character attributes such as ‘round’ and ‘harsh’ were found to significantly depend on bitterness and aroma levels, with the second level of aroma addition (245 mg/L) giving a ‘rounded’ bitterness in low bitterness beers but ‘harsh’ bitterness in high bitterness beers. The impact of aroma on temporal bitterness was also confirmed with time-intensity measurements, and found to be mostly significant at the highest level of hop aroma addition (490 mg/L) in low bitterness beers. These findings represent a significant step forward in terms of understanding bitterness flavour perception and the wider impact of hop compounds on sensory perception.